FINANCIAL CRIME IN THE ROMANIAN BANKING SYSTEM - LUMINIŢA DRAGNE; GEORGE DOREL MATEI; ANAMARIA TRANCA (Challenges of the Knowledge Society, 2012)
The crime in the financial and banking system, through the disasters it produces, damages and large amount of victims, generates the largest economy damages, both national and international level. This phenomenon occurs and is manifested in a specific environment, the economy and finances one, takes different forms and operates with appropriate techniques. Most of the times, the banking system from Romania, has been used for personal grounds, which leads to serious damage of the Romanian economy. Insufficiently matured economic or imperfect judicial environments are only some of the factors that led to the commission of crimes in this area. Also, this type of crime has been determined, among other things, by the economic status, the social structure or the stage of development of the society.